OPTIMISATION OF PULSE FORMING NETWORKS - kale, ayush (IJRDO - Journal of Electrical And Electronics Engineering, 2021)
This study presents reliable optimization techniques for Pulse Forming Networks (PFN). Pulse Forming Networks (PFN) are used to generate train of high peak power short duration pulses. They only store the energy necessary for a single pulse and discharge it into the load in the correct pulse form. The required energy is  stored in combinations of capacitors and inductors as the circuit elements. The shape generated by PFN is not ideal and PFNs can be designed with better Pulse Performance by doing modifications and using techniques which can improve the desired output pulse shape and overall energy efficiency of the network.In this study, two different techniques, Green’s Function to calculate the input voltage for the desired ideal pulse and Particle Swarm Optimization (PSO) for optimizing the inductor values have been used for optimization of PFN and its performance has been simulated using MATLAB/Simulink.